Body shape variation in two species of darters (Etheostoma, Percidae) and its relation to the environment. Issue 1 (7th August 2015) - Hopper, Garrett W.; Morehouse, Reid L.; Tobler, Michael
Abstract: Environmental variation can shape phenotypic variation in organisms, but most evidence for trait differentiation comes from analyses of dichotomous habitat types that differ in only one or few key environmental factors. In reality, environmental variation is often more subtle, gradual and multifarious. Here, we investigated geographic variation in body shape of two darter species ( Etheostoma spectabile and Etheostoma flabellare ; Percidae) that occur along river gradients. This study addressed three specific questions: Is there intraspecific geographic variation in the two species across different sites in the Ozark Highlands of Oklahoma (USA)? Is phenotypic variation across sites correlated with abiotic environmental conditions? Do the two species share site‐specific (i.e. convergent) phenotypic variation in areas where they occur together? Our results indicated significant body shape variation in both species. Population differences in body shape were particularly correlated with variation in substrate composition. The combined analysis of both species indicated a small but significant effect of convergence on body shape wherever they are sympatric; shared variation, however, was not related to any environmental variables included in the analysis. While it remains unclear whether phenotypic variation in these species is due to heritable differentiation or environmentally induced plasticity, our results indicate that even subtle and gradual environmental variation can induce substantial variation in phenotypes on a relatively small spatial scale.